Variation in the inter-service intervals of UK dairy cows - Remnant, J.G.; Green, Martin J.; Huxley, Jonathan; Hudson, C.D. (American Dairy Science Association, 2015)
An understanding of the normal estrous cycle length of the cow is important when managing and monitoring dairy herd fertility. Whilst the normal inter-ovulatory interval is widely considered to be 21 days, some studies have found alternative intervals to be more prevalent; previously most of the variation in interval length was expected to be between cows. The aim of this study was to assess the time between inseminations (inter-service interval, ISI), in a large number of dairy cows and to explore possible associations between cow factors and estrous cycle length. The study used ISI data from 42,252 cows in 159 herds across England and Wales. Univariate analysis of the subset of 114,572 intervals between 15 and 30 days (a range covering the increased frequency of ISIs occurring at the expected time of the first return to estrus) following an insemination revealed a modal ISI of 22 days. Primiparous heifers had a modal ISI of 21 days. There were significant differences between the distribution of ISIs for different yield groups, parity numbers and the number of inseminations. Multilevel regression modelling was used to evaluate the associations between cow factors and ISI, whilst accounting for clustering at the herd and cow level. This revealed significant associations between predicted ISI and insemination number, days in milk, lactation 305 day milk yield, and month and year of insemination. Variance partition coefficients indicated that only 1% of variation in ISIs was at the herd level, 12% at the animal level and 87% at the insemination level, indicating that cycle length varies substantially more between cycles within a cow than between cows or herds. These findings suggest the “normal” range of ISI for modern UK dairy cows is longer than expected and that there is a large amount of unexplained variation in cycle length within individual animals over time.